2014
DOI: 10.1186/2046-9063-10-9
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of high affinity potassium transporter (HKT) isoforms in different plants

Abstract: BackgroundHigh affinity potassium transporters (HKTs) are located in the plasma membrane of the vessels and have significant influence on salt tolerance in some plants. They exclude Na+ from the parenchyma cells to reduce Na+ concentration. Despite many studies, the underlying regulatory mechanisms and the exact functions of HKTs within different genomic backgrounds are relatively unknown. In this study, various bioinformatics techniques, including promoter analysis, identification of HKT-surrounding genes, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Such findings have also been made in sunflower by Manavella et al (2008). Skn-1_modif is a cis-acting regulatory element required for endosperm expression and MSA-like is required for cell cycle regulation (Babgohari et al 2014). Transcription factors could be found in the promoter region involved in shoot-specific expression and response to light (as-2-box) (Fig.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Such findings have also been made in sunflower by Manavella et al (2008). Skn-1_modif is a cis-acting regulatory element required for endosperm expression and MSA-like is required for cell cycle regulation (Babgohari et al 2014). Transcription factors could be found in the promoter region involved in shoot-specific expression and response to light (as-2-box) (Fig.…”
Section: Discussionsupporting
confidence: 60%
“…In plants, TFs have important impacts on developmental processes, cellular physiology, and responses to environmental signals (Chow et al 2016). The promoter regions regulating the MmPIP2 gene may be conserved, as it has been reported that there are two AP-1 binding sites (TATA-box) and one CAAT-box in common cis-acting elements in promoter and enhancer regions, and a greater number of TATA boxes in the promoter region can result in higher expression of the gene (Babgohari et al 2014) and the CAAT-box has been demonstrated to have a positive effect on frequency of transcriptional initiation Fig. 1.…”
Section: Discussionmentioning
confidence: 99%
“…The developed transcriptomic signature of successful AM colonization of roots of Medicago truncatula , obtained by integration of meta-analysis and machine learning (attribute weighting) models, was used for upstream regulatory analysis through common regulator discovery, as previously described (Deihimi et al, 2012 ; Babgohari et al, 2014 ; Bakhtiarizadeh et al, 2014b ; Shamloo-Dashtpagerdi et al, 2015 ). To this end, the top 20 highly upregulated meta-genes, which responded to AM inoculation, (Supplementary Table 5 ) were selected for promoter analysis and common transcription factor discovery.…”
Section: Methodsmentioning
confidence: 99%
“…MYB binding sites are abundant in promoters of stress responsive genes, however there are some evidence that they work together with other proteins to confer light responsiveness (Babgohari et al, 2014). MYB15 is R2R3 type MYB transcription factor involved in cold regulation of number of genes (Mahdi et al, 2013).…”
Section: Case Study 1: Comparative Promoter Analysis Of Atham1 and Atmentioning
confidence: 99%
“…Recently, we developed a new approach for gene discovery irrespective from gene coding (BLAST), based on identifying distinct organization and combination of CREs (in view of order and distance) on promoter regions and identification of the genes with similar promoter architecture within whole genome (Hosseinpour et al, 2013). Recently, it has been demonstrated that CREs on the promoter regions of genes in wild wheat are more variable and frequent than the cultivated wheat which contributes in fast response and better understanding of environmental conditions for wild genotype (Babgohari et al, 2014). Due to the unique characteristic of transcription factors in binding to CREs on promoter regions of different genes, a small number of transcription factors are enough to regulate a considerable number of genes and play the central role in functional genomics (Mahdi et al, 2013;Mahdi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%